An investigation into the importance of the quantity and quality of the mother-child relationship in preschool children - Ross, Annette (My University, 2015)
The present study aimed first, at determining whether part-time (nursery-school attendance), and a full-time (day-care attendance) quantitative disruption in motherchild interaction, affects the child’s separation anxiety, stranger anxiety, frustration tolerance and general coping mechanisms. Second, the effect of the quality of mothering (the degree of maternal acceptance and responsiveness) on the child's separation anxiety, stranger anxiety, frustration tolerance and general coping mechanisms was assessed. Thirdly and fourthly, this study aimed at determining whether the age and the sex of the child affect the separation anxiety, stranger anxiety, frustration tolerance and general coping mechanisms exhibited by that child; and finally whether there is a relationship between separation anxiety, stranger anxiety, frustration tolerance and general coping mec hanisms. Fifty-six four-year-olds and their mothers were observed. These included 14 children who stayed home with their mothers; 14 children attending nursery-school; 14 children attending a day-care centre from the age of three; and 14 children attending a day-care centre froc the age of one. A problem-solving task was administered to the children to obtain a measure of their frustration tolerance; a modified version of the Ainsworth-Wittig Strange-Situation Procedure was employed to measure the children's separation anxiety and stranger anxiety;
A dissertation submitted to the Faculty of Arts University of the Witwatersrand, in partial fulfilment of the degree of Master of Arts (Clinical Psychology). Johannesburg, 1981
Keywords: Mother and child--Psychological aspects.; Parent and child.; Preschool children--Psychology.